Income, wealth and earnings inequality in Australia Evidence from the HILDA survey - Sila, Urban (OECD Publishing, 2019)
This paper analyses income, wealth and earnings inequality in Australia, using the Household, Income and Labour Dynamics in Australia (HILDA) Survey as the primary source of data. Income inequality in Australia has risen in the last two decades, but most of the rise occurred prior to the global financial crisis. HILDA data nevertheless show evidence of slower income growth in the middle of the income distribution compared with the top and the bottom. While Australia has experienced a rising inequality in wages - mostly through rapid earnings increases among top earners - this has been offset by increased participation and longer hours worked at the bottom of the distribution. According to HILDA data, relative pay across different levels of education groups has not recorded large shifts over the last 15 years. At the same time, we find evidence for job polarisation; notably, the share of high skilled jobs versus middle skilled jobs has increased. With respect to concerns about the casualisation of the labour force and less stable nature of jobs amid technological change and globalisation, the incidence of casual employment - where workers receive no paid sick leave or holiday leave - in Australia has been reported to have risen since the 1980s, especially for females. According to HILDA data however, the incidence of casual employment has fallen since early 2000s. Furthermore, we find no evidence that contract duration has shortened over time
Keywords: Economics; Australia